2021
DOI: 10.1111/ina.12816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of survival rates of airborne microorganisms on the filter layers of commercial face masks

Abstract: After the WHO designated COVID-19 a global pandemic, face masks have become a precious commodity worldwide. However, uncertainty remains around several details regarding face masks, including the potential for transmission of bioaerosols depending on the type of mask and secondary spread by face masks. Thus, understanding the interplay between face mask structure and harmful bioaerosols is essential for protecting public health. Here, we evaluated the microbial survival rate at each layer of commercial of filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Surgical masks are regulated as medical devices and FFP masks as respiratory protection device and are designed to meet more demanding performance criteria. In their work to evaluate the survival rate of bio aerosols on filter layers of FFPs and surgical masks, Jeong et al 12 showed that FFPs were more effective in physically blocking bio aerosols and thus showed lower portion of microbial viability compared to surgical masks.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical masks are regulated as medical devices and FFP masks as respiratory protection device and are designed to meet more demanding performance criteria. In their work to evaluate the survival rate of bio aerosols on filter layers of FFPs and surgical masks, Jeong et al 12 showed that FFPs were more effective in physically blocking bio aerosols and thus showed lower portion of microbial viability compared to surgical masks.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al ( 2021) determined that the survival rates of Staphylococcus epidermidis in bioaerosols from facepieces and surgical mask filters to be 13% [20]. Lin et al (2017) also reported that the viability of airborne B. subtilis spores filtered on facepieces and surgical masks increased by over 100% when they were stored at 37 • C with a relative humidity of 95% for 24 h, i.e., in conditions similar to those of a used mask [21].…”
Section: Viability Of B Subtilis From Airborne Bioaerosols Filtered O...mentioning
confidence: 99%
“…On the other hand, more such bioaerosols were trapped by the anti-droplet masks than passed through them due to the great filtration performance of these masks against airborne droplets containing bacteria. Nevertheless, wearing masks even with high filtration performance may also allow for the transmission of respiratory disease if these masks are inappropriately used, such as when their surfaces are touched by the hands of the user [20][21][22]. Therefore, misusing masks poses risks to health as a result of bioaerosols passing through them or from the survival of living components on the masks, or from both.…”
Section: Viability Of B Subtilis From Airborne Bioaerosols Filtered O...mentioning
confidence: 99%
“…However, there are differences in filter efficiency and protective ability among the various types of masks on the market [13,14]. Researchers found that the survival rate of most bacterial particles in mask filtration layers (such as filter cores) can reach 44 to 77% [15]. Ordinary masks worn by most people are less effective at stopping microorganisms, and simply wearing a mask cannot guarantee absolute safety.…”
Section: Introductionmentioning
confidence: 99%